Rights of People with Disabilities in the Qur'an and Hadith from the Perspective of Fiqh Awlawiyyat - Muhammad Kudhori; Masruri, Ulin Niam; Azizah, Ma’rufatul; El-Hanim, Syarifah (The Center for Disability Studies and Services Brawijaya University, 2024)
Disabled groups still often receive discriminatory treatment in society. Discriminatory treatment occurs in various sectors, such as education and the world of work. In fact, as humans created by Allah Swt. Disabled groups should also have the same rights as humans in general. This research seeks to reveal the rights of disabled groups in the Al-Qur'an and the Hadith of the Prophet saw. awlawiyyāt fiqh perspective. This research is qualitative research that utilizes library sources (library research) with content analysis and descriptive-analytical analysis as the data analysis method. The results of this research show that the rights of disabled groups in the Al-Qur'an and Hadith include all the rights that humans in general have. In the review of awlawiyyāt jurisprudence, these rights must receive priority in service, because disabled groups need these rights more than humans in general. Implementation of the rights of persons with disabilities in the awlawiyyāt fiqh review is carried out by prioritizing services for them by providing facilities that can support their lives better.